Sexual Function and Quality of Life in Iranian Women With Human Papillomavirus Infection - Afsaneh Tehranian; Marzieh Vahid Dastjerdi; Sare Hatamian; Akram Ghahghaei-Nezamabadi (Tehran University of Medical Sciences, 2024)
Objective: Considering the prevalence of Human Papillomavirus (HPV) infection and the lack of HPV vaccination program in Iran among young women and the importance of quality of life and sexual performance in women, we decided to conduct a study to examine the relationship between HPV infection and sexual dysfunction and quality of life in Iranian women. Materials and methods: In this cohort study, 250 married women who infected with HPV were recruited via convinence sampling from colposcopy clinic of Arash women hospital (Tehran, Iran) from April 2020 to May 2022.They were evaluated concerning their sexual function in the domains of desire, arousal, lubrication, orgasm, satisfaction and pain with the female sexual function index (FSFI) questionnaire (the total FSFI score is calculated by the sum of the nineteen items). Sexual quality of life-female (SQOL-F) items (Likert-type scale with a cut-off of 65 points) were organized into four sub-scales: psychosexual feelings, sexual and relationship satisfaction, self-worthlessness, and sexual repression. All patients filled out the female sexual function index (FSFI) and sexual quality of life (SQOL) questionnaires. Variables were analysed via correlation coefficient and linear regression tests. Results: Mean age and mean marriage duration were 38.5±4.5 and 12.2±7.2, respectively. There was a weak correlation between FSFI and SQOL (r=0.15, p=0.001).Time of marriage and genital warts were the predictors on the FSFI and SQOL. Conclusion: The findings suggest that HPV infection can impair sexual function and quality of life. This research contributes valuable insights, especially considering the prevalence of HPV.